The brazilian biodiesel program and regional development: cases from northern Brazil - Finco, Marcus Vinicius Alves; Doppler, Werner (Redes, 2011)
Biofuel production has been greatly discussed in Brazil. In 2004, these debates led the country to develop new policies and implement a national program for biodiesel use and production (PNPB) with the intent to increase the share of renewable energy and foster regional development. In this context, the present study aims to assess the impacts of PNPB on regional development in Tocantins State, northern Brazil. For this purpose, ranges of socio-economic indicators were collected among national and regional stakeholders, as well as specific literature. The preliminary results point out that distribution logistics appears to be a considerable constraint to the success of the PNPB. The concentration of biodiesel industries in the central-west region of the country, and the large distances to deliver biodiesel in the northern Brazil make biodiesel prices non-competitive when compared to fossil diesel. The results also suggest that the PNPB is not succeeding in promoting the integration of family agriculture in the Tocantins state, especially due to the structural difficulty of the agricultural sector, as well as the technical and political shortcomings presented by the mechanism of incentives.